2021
DOI: 10.1182/blood-2021-150757
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 First-in-Human Study of Tnb-383B, a BCMA x CD3 Bispecific T-Cell Redirecting Antibody, in Patients with Relapsed/Refractory Multiple Myeloma

Abstract: Background Prognosis is poor for patients (pts) with relapsed/refractory multiple myeloma (RRMM; median overall survival: <1 year), indicating a clear need to identify agents with novel mechanisms of action. B-cell maturation antigen (BCMA) has recently emerged as a novel treatment target for MM due to its highly selective expression in plasma cells. TNB-383B, a BCMA x CD3 T-cell engaging bispecific antibody, was designed to overcome the toxicity limitations of existing BCMA therapies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Haematological toxicity was common, along with Grades 1–2 CRS (72%, being almost always limited to priming and first dose), and CRS Grade ≥3 developed in a single patient (<1%). Other BCMA × CD3 TCEs include Tnb‐383B (ABBV‐383), 43 REGN5458, 44 and CC‐93269 45 . Their preliminary efficacy and safety are summarised in Table 1.…”
Section: Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haematological toxicity was common, along with Grades 1–2 CRS (72%, being almost always limited to priming and first dose), and CRS Grade ≥3 developed in a single patient (<1%). Other BCMA × CD3 TCEs include Tnb‐383B (ABBV‐383), 43 REGN5458, 44 and CC‐93269 45 . Their preliminary efficacy and safety are summarised in Table 1.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…We believe that given the dismal prognosis of TCR MM, the lack of a clearly superior and widely available therapy, and the absence of high-level evidence in this setting, it is imperative to offer such patients enrolment in therapeutic clinical trials whenever possible. Here we summarise clinical data on different drugs, combinations and approaches (Table 1) [35][36][37][38][39][40][41][42][43][44][45][46] employed in this setting and suggest an algorithm to guide choice of therapy (Figure 1).…”
Section: Tr E Atm E N T Op Tionsmentioning
confidence: 99%
“…T-cell redirecting bispecific antibodies are an off-the-shelf, steroid-sparing, novel immunotherapy drug class with great potential to change the MM treatment landscape. The constructs closest to routine clinical use are designed to simultaneously bind CD3 on T-cells and a specific target epitope on the MM cell the current majority target BCMA and are still investigational at this time, these include AMG701, 91 teclistamab, 92 elranatamab, 93 ABBV-383B, 94 and REGN5458, 95 while talquetamab targets GPRC5D 96 ( Table 6 ). Despite the fact that there are currently no FDA-approved bispecific antibodies, these drugs are moving through phase I and II trials and are actively being investigated in randomized phase III trials.…”
Section: Next-generation Non-fda-approved Therapeutics In Clinical Tr...mentioning
confidence: 99%
“…Despite the fact that there are currently no FDA-approved bispecific antibodies, these drugs are moving through phase I and II trials and are actively being investigated in randomized phase III trials. 91 , 93 , 94 , 96 98 …”
Section: Next-generation Non-fda-approved Therapeutics In Clinical Tr...mentioning
confidence: 99%
“…In an update of the phase I dose-expansion study, an ORR of 77% was observed at doses ≥40 mg. Cytokine release syndrome (CRS) was seen in around 52% of patients, mostly grades 1 and 2. 45 Teclistamab is another BCMA x CD3 bispecific antibody engineered to enhance the immune response against tumour cells by binding to CD3…”
Section: Therapies In Relapsed Refractory Multiple Myelomamentioning
confidence: 99%